(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Aggressive open lumbar discectomy is the most commonly performed surgical procedure for patients with persistent low back and leg pain. In this retrospective study, 1,380 patients were evaluated for long-term results of aggressive discectomy for the single level lumbar disk herniation. Demographic data, surgical data, complications and reherniation rate were collected and clinical outcomes were assessed using visual analogue score (VAS), Oswestry disability index (ODI) and modified Mcnab criteria. The mean follow-up period was 28.8 months. According to the modified Mcnab criteria, the long-term results were excellent in 640 cases, good in 445 cases, fair in 255 cases, and poor in 40 cases. The mean VAS scores for back and radicular pains and ODI at the end of 2 years were 1.1 ± 1.0, 1.5 ± 0.5 and 6.6 ± 3.1% respectively. The complications were foot drop (n=7), dural tear (n=14), superficial wound infection (n=17), discitis (n=37) and reherniation (n=64). The dural tear and superficial wound infections resolved after treatment but 28 discitis patients were treated by conservatively and the remaining 9 underwent surgery. Among reherniation patients, 58 underwent revision discectomy and 4 underwent transforaminal lumbar interbody fusion and stabilization. Aggressive discectomy is an effective treatment of lumbar disk herniation and maintains a lower incidence of reherniation but leads to a collapse of disc height and in long run gives rise to intervertebral instability and accelerates spondylosis.